2018
DOI: 10.1080/09553002.2018.1440092
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of inflammatory responses to radiation and normal tissues toxicity: clinical implications

Abstract: The early inflammation during the radiation treatment is often a limiting factor in radiotherapy. In addition to the limiting factors, chronic inflammatory responses may increase the risk of second primary cancers through continuous free radical production, attenuation of tumor suppressor genes, and activation of oncogenes. Moreover, these effects may influence non-irradiated tissues through a mechanism named bystander effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 327 publications
3
79
0
Order By: Relevance
“…It is confirmed that inflammatory responses to cancer therapy may lead to chronic oxidative stress, which may lead to damage to the normal function of organs. Also, it may cause accumulation of unrepaired DNA damage, leading to genomic instability and cancer (Najafi, Motevaseli, et al, ). Inflammation can induce reduction–oxidation reactions, which itself play a key role in triggering of inflammation responses.…”
Section: Protection Against Inflammation In Response To Radiation Andmentioning
confidence: 99%
“…It is confirmed that inflammatory responses to cancer therapy may lead to chronic oxidative stress, which may lead to damage to the normal function of organs. Also, it may cause accumulation of unrepaired DNA damage, leading to genomic instability and cancer (Najafi, Motevaseli, et al, ). Inflammation can induce reduction–oxidation reactions, which itself play a key role in triggering of inflammation responses.…”
Section: Protection Against Inflammation In Response To Radiation Andmentioning
confidence: 99%
“…Given that NO could lead to nitroace‐tylation and inactivation of Ogg1, these events resulted in downregulation of other downstream genes (ie, X‐ray repair cross‐complementing 1 (Xrcc1) and apurinic/apyrimidinic endodeoxyribo‐nuclease 1 [Apex1]). In this regard, NO can induce the accumulation of DNA damage and the promotion of genomic instability . It has been shown that melatonin accelerates the kinetics of DNA repair following exposure of DNA to ROS .…”
Section: Anticancer Features Of Melatoninmentioning
confidence: 99%
“…Besides the direct action of melatonin, this agent enables neutralizing free radicals through induction of suppression of redox enzyme activity (DUOX1&2, NOX2&4, iNOS, and mitochondria derived ROS) or antioxidant enzymes . Therefore, these features make melatonin a potential therapeutic agent for radioprotection during radiotherapy or exposure to nuclear or radiological pollutants or warfare …”
Section: Anticancer Features Of Melatoninmentioning
confidence: 99%
See 2 more Smart Citations